Probing potential active sites and bipolar electric-field effects: Novel insights into the Li+ extraction mechanism on MoS2 in aqueous capacitive deionization - Xueli Zhang; Linhui Jia; Bing Chang; Dezhi Fang; Chengxing Cui; Silu Huo; Shuaiqi Ding; Yu Chen; Yang Li; Zhiyuan Chen; Runqiang Liu; Kexun Li (Desalination, 2026)

NIR-induced photothermal effects for enhanced uranium uptake and anti-biofouling by PAO-based micromotors - Xinle Zhang; Linhui Fu; Ling Chen; Kai Feng; Jian Fu; Yiqi Zhang; Jiang Gong; Yuping Zhang; Ran Niu (Chemical Engineering Journal, 2026)

The poisoning mechanism of N2O reductive catalysts and anti-interference modification/regeneration technology - Wu Pengfei; Guan Bin; Zhu Lei; Zhu Tiankui; Chang Shiying; Ma Jiangli; Wang Rong; Yang Dongxia; Shu Kaiyou; Zhuang Zhongqi; Chen Junyan; Gao Junjie; et al. (Journal of Environmental Chemical Engineering, 2026)

Tea-woody plant intercropping improves soil quality and ecosystem multifunctionality in the acidic tea plantation system - Linhui Wang; Jiabao Han; Xiangde Yang; Kang Ni; Lifeng Ma; Yuanzhi Shi; Yaqin Long; Linbo Chen; Jianyun Ruan; Shiwei Guo (Journal of Environmental Management, 2026)

Urban features dominate hot spots of extreme heat and elevate heat-related morbidity in 2024 over Yangtze River Delta - Siyang He; Jiacan Yuan; Chen Liang; Yuanhao Chen; Xiangyu Ao; Linhui Li; Alexander Baklanov; Renhe Zhang (Urban Climate, 2026)

Comparative evaluation of imbalanced data processing models for albacore tuna fishing ground prediction: a case study in the waters near Cook Islands - Liming Song; Chen You; Linhui Wang; Meng Zhang; Shun Wang (Fisheries Science, 2026)

Linking lunar cycles to yellowfin tuna catchability: A multi-pathway ecological framework in the waters near the Marshall Islands - Linhui Wang; Liming Song; Tchgom Manga Josué; Chen You; Shun Wang; Jieran Shen (Regional Studies in Marine Science, 2026)

SOC1 clade genes coordinate lateral root development and response to multiple phytohormonal and environmental stress signals in Arabidopsis - Xinyue Li; Qian Ma; Ping Jin; Yaxuan Wang; Tongyao Yang; Ying Chen; Shujuan Guo; Zisheng Zhang; Chengbin Xiang; Qiuling Wang; Linhui Yu (Journal of Plant Physiology, 2026)

Cerium-modified Cu-SSZ-13 catalysts: Enhanced low-temperature activity and hydrothermal stability for efficient NOx reduction - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

Research on emission control performance of SSCR system based on multi-condition operation and three-high tests - Bin Guan; Kaiyou Shu; Lei Zhu; Tiankui Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

Developing a multi-task quantitative structure-activity relationship (QSAR) model for predicting the toxicity potential of chemicals used in e-cigarette products - Alexa Canchola; Kunpeng Chen; Md Ziaur Rahman; Lillian Tran; Wonsik Woo; Linhui Tian; Ying-Hsuan Lin; Wei-Chun Chou (Journal of Hazardous Materials, 2026)

The role of ammonia in the global energy transition: opportunities and challenges in ammonia gas turbine technology - Shuai Chen; Bin Guan; Lei Zhu; Zhongqi Zhuang; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; et al. (Fuel, 2026)

High-efficiency catalytic removal of N2O from ammonia-fueled engine exhaust - Bin Guan; Zhongqi Zhuang; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Junjie Gao; Kaiyou Shu; Hongtao Dang; Luyang Zhang; Tiankui Zhu; et al. (Fuel, 2026)

Isostructural passivation strategy by 4,4′,4″-nitrilotribenzoic acid enhance interfacial compatibility for high-efficiency perovskite solar cells - Pihuang Yang; Ligang Yuan; Yuyan Dong; Linhui Tang; Junhong Duan; Weiqing Liu; Jianwei Chen; Chaohui Xiong; Ying Liu; Yan Liu; Wenhao Chen; Keyou Yan (Chemical Engineering Journal, 2026)

Precision interface architecture of zinc anodes for highly reversible Zn-metal batteries - Xijun Liu; Le Zhang; Xiaoru Chen; Linhui Chang; Zhifeng Xu; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2026)

P2X7 Receptor Inhibition Mitigates Microglial Activation, Neuroinflammation, and Secondary Thalamic Damage After Ischemic Stroke - Xiaomei Wu; Ming Gong; Linhui Peng; Caimin Chen; Zhiqiang Hu; Weiwen Sun; Xialin Zuo (Molecular Neurobiology, 2026)

Ion exchange-based magnetic micro-cleaners harness multiple effects to enhance antibiotics removal - Ling Chen; Linhui Fu; Xinle Zhang; Jiang Gong; Jinping Qu; Ran Niu (Water Research, 2025)

Substituted diphenylamine antioxidants and synthetic phenolic antioxidants in leachate from domestic landfills in China: Occurrence and removal via treatment - Linhui Zhang; Fei Chen; Xianming Zhang; Xue Zhang; Bin Liang; Shanshan Bai; Zifeng Zhang; Yifan Li; Nanqi Ren (Journal of Hazardous Materials, 2025)

Flexible CeO₂ surface engineering optimizes atomically dispersed Ru catalyst-support interaction for enhanced ammonia decomposition - Xuehan Hu; Bin Guan; Lei Zhu; Chenyu Zhu; Zhongqi Zhuang; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Occurrence characteristics, source analysis, and risk assessment of microplastics in agricultural soils: A case study on Shihezi Reclamation Area, Xinjiang, China - Zhifeng Jia; Linhui Zhang; Yanhua Wang; Jialu Pang; Jia Chen; Tianhao Zhang; Wei Wei (Science of The Total Environment, 2025)

Study on the electric field and current intensity in lightning discharge channel based on the Hα broadening - Linhui Chen; Ping Yuan; Rubin Jiang; Tingting An; Hong Deng (Atmospheric Research, 2025)

Photothermal-driven micromotor for enhanced lithium extraction from salt-lake brines - Shihao Ding; Wenqian Xing; Ling Chen; Linhui Fu; Xinle Zhang; Zhen Luo; Qianqian Li; Mengting Qin; Jiang Gong; Jinping Qu; Ran Niu (Chemical Engineering Journal, 2025)

Pd/F-Al2O3 catalyst for N2O-NH3-SCR with ultrahigh low-temperature activity and resistance to inhibitory gases: Property research of being rich in oxygen vacancies with free electrons and reaction mechanisms - Zhongqi Zhuang; Bin Guan; Lei Zhu; Xuehan Hu; Chenyu Zhu; Sikai Zhao; Junyan Chen; Kaiyou Shu; Hongtao Dang; Junjie Gao; Luyang Zhang; Tiankui Zhu; et al. (Chemical Engineering Journal, 2025)

Single-Cell RNA Sequencing Delineates the Atlas and Cell Interactions of the Testicular Cells in Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Jingting Yao; Sendong Li; Wenzhuo Ban; Linhui Zeng; Han Cui; Kaili Chen; Hongyan Xu (Marine Biotechnology, 2025)

Investigation of soil physical, chemical and biological indicators in industrial towns: a case study in a Chinese town - Caixia Liu; Qingying Gao; Shuhe Zhang; Linhui Liao; Jingjing Chen; Liang Wang (Environmental Geochemistry and Health, 2025)

Novel impact of metal ion-induced cell death on diabetic cardiomyopathy pathogenesis and therapy - Jingjing Jiang; Shengnan Hu; Kaibo Hu; Leyang Xiao; Jitao Lin; Yixuan Chen; Deju Zhang; Yangliu Ou; Jing Zhang; Linhui Yuan; Wenting Wang; Peng Yu (Apoptosis, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Prediction on Yellowfin Tuna ( Thunnus albacares ) Fishing Ground in Waters Near the Marshall Islands Based on SMOTETomek‐RF - Meng Zhang; Liming Song; Chen Pan; Linhui Wang (Fisheries Oceanography, 2025)
This study monitored 37 longliners fishing in waters near the Marshall Islands from 2020 to 2022 by Liancheng Overseas Fishery (Shenzhen) Co., Ltd.'s operation management system. This study developed nine predictive models on the relationship between catch per unit effort (CPUE) data for yellowfin tuna ( Thunnus albacares ) and the environmental data. The environmental data integrate 48 variables, including eddy kinetic energy, chlorophyll a concentration, sea surface height, and additional measures of vertical oceanic conditions, alongside spatiotemporal parameters (year, month, day, longitude, and latitude). This study employed four spatial resolutions (0.25° × 0.25°, 0.5° × 0.5°, 1° × 1°, and 2° × 2°) to develop nine predictive models: KNN, RF, GBDT, CART, LightGBM, XGBoost, CatBoost, AdaBoost, and Stacking (RF, KNN, GBDT, and LR). These models, with a daily time resolution, were trained using 75% of the data and tested with the remaining 25%. The optimal spatial resolution and model were determined through a comprehensive comparison of model evaluation metrics across these spatial resolutions. The SMOTETomek algorithm was then applied to resample 75% of the data at the optimal spatial resolution, forming a new training dataset. This dataset was used to refine the model, subsequently tested with the remaining 25% of the data. Results indicated that (1) the optimal spatial resolution is 0.25° × 0.25° and the optimal model is RF; (2) the SMOTETomek algorithm enhances the model's predictive performance; and (3) the developed SMK‐RF model, exhibiting Acc and AUC values of 76.73% and 82.47%, respectively, accurately predicts the central fishing grounds for yellowfin tuna, consisting closely with actual fishing activity.

Selenium nanoparticles modified with Ophiocordyceps gracilis polysaccharides: Enhancing stability, bioavailability, and anti-inflammatory efficacy - Xinya Qi; Lingling Tong; Hui Lian; Zilei Chen; Linhui Yang; Yang Wu; Suxing Jin; Dongsheng Guo (Food Research International, 2025)

Ion-exchange induced multiple effects to promote uranium uptake from nonmarine water by micromotors - Linhui Fu; Kai Feng; Qianqian Li; Mengting Qin; Jing Yang; Xinle Zhang; Ling Chen; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

Thermal transformations of perfluorooctanoic acid (PFOA): Mechanisms, volatile organofluorine emissions, and implications to thermal regeneration of granular activated carbon - Junli Wang; Lillian N. Tran; Jose Mendoza; Kunpeng Chen; Linhui Tian; Yuwei Zhao; Jinyong Liu; Ying-Hsuan Lin (Journal of Hazardous Materials, 2024)

6-Phosphogluconate dehydrogenase 2 bridges the OPP and shikimate pathways to enhance aromatic amino acid production in plants - Qian Tang; Yuxin Huang; Zhuanglin Shen; Linhui Sun; Yang Gu; Huiqing He; Yanhong Chen; Jiahai Zhou; Limin Zhang; Cuihuan Zhao; Shisong Ma; Yunhai Li; et al. (Science China Life Sciences, 2024)

Exploring the material basis and molecular targets of Changma Xifeng tablet in treating Tourette syndrome: an integrative approach of network pharmacology and miRNA analysis - Jing Peng; Qiaoling Li; Linhui Liu; Ping Gao; Lipeng Xing; Li Chen; Hui Liu; Zhisheng Liu (Metabolic Brain Disease, 2024)

Strategies and mechanisms for improving groundwater remediation efficiency of chlorinated ethenes by controlling the particle size of polyhydroxyalkanoate - Jie Ma; Linhui Lei; Zhiwei Gong; Zongping Wang; Hui Liu; Guanghao Chen; Gang Guo (Chemical Engineering Journal, 2024)

Downregulating DNA methyltransferase 3B by suppressing the PI3K/Akt signaling pathway enhances the chemosensitivity of glioblastoma to temozolomide - Wenwu Kan; Linhui Gao; Jingnan Chen; Li Chen; Guojun Zhang; Bilie Hao; Min He; Xudong Chen; Cheng Wang (Molecular Neurobiology, 2024)
Glioblastoma (GBM) is the most common malignant brain tumor and has the poorest prognosis attributed to its chemoresistance to temozolomide (TMZ), the first-line drug for treating GBM. TMZ resistance represents a significant obstacle to successful GBM treatment, necessitating the development of new strategies to overcome this resistance and augment the chemosensitivity of GBM cells to TMZ. This study established a TMZ-resistant U251 (U251-TMZ) cell line by exposing it to increasing doses of TMZ in vitro. We focused on the DNA methyltransferase 3B (DNMT3B) gene, phosphorylated Akt (p-Akt), total Akt (t-Akt), phosphorylated PI3K (p-PI3K), and total PI3K (t-PI3K) protein expression. Results showed that the DNMT3B gene was significantly upregulated in the U251-TMZ cell line. The p-Akt and p-PI3K protein expression in U251-TMZ cells was also significantly elevated. Moreover, we found that DNMT3B downregulation was correlated with the increased chemosensitivity of GBM cells to TMZ. LY294002 suppressed the PI3K/Akt signaling pathway, leading to a notable inhibition of PI3K phosphorylation and a significant decrease in DNMT3B expression in U251-TMZ cells. Given that DNMT3B expression is mediated by the PI3K/Akt signaling pathway, its downregulation further increased the chemosensitivity of GBM cells to TMZ and therefore is a promising therapeutic for GBM treatment. Our results suggested that DNMT3B downregulation can inhibit the proliferation of GBM cells and induce GBM cell apoptosis in vitro. In addition, the PI3K/Akt signaling pathway plays an important role in the chemosensitivity of GBM cells to TMZ by regulating DNMT3B expression.

Interaction and selective treatment of lead-zinc flotation wastewater for wastewater recycling using ectrocatalytic internal micro-electrolysis - Hongyan Ma; Chen Jiang; Xuan Zhu; Xin Zheng; Wenyi Zhou; Lirong Wang; Ming Zhao; Linhui Feng; Xiaojun Xu; Ciming Kong; Tianguo Li (Journal of Cleaner Production, 2024)

Exploring the relationship between lightning discharge current and plasma spectrum - Hong Deng; Facai Su; Ping Yuan; Baoyu Chen; Tingting An; Linhui Chen; Yingying An; Guorong Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Monitoring system for peanut leaf disease based on a lightweight deep learning model - Yongda Lin; Linhui Wang; Tingting Chen; Yajia Liu; Lei Zhang (Computers and Electronics in Agriculture, 2024)

Dual-functional metal-organic frameworks-based hydrogel micromotor for uranium detection and removal - Xinle Zhang; Ling Chen; Linhui Fu; Kai Feng; Jiang Gong; Jinping Qu; Ran Niu (Journal of Hazardous Materials, 2024)

Lightweight green citrus fruit detection method for practical environmental applications - Jianqiang Lu; Pingfu Chen; Chaoran Yu; Yubin Lan; Linhui Yu; Ruifan Yang; Hongyu Niu; Huhu Chang; Jiajun Yuan; Liang Wang (Computers and Electronics in Agriculture, 2023)

Quantification and characterization of microplastics in farmland soils of Jiangsu Province, East China - Bingqing Zhu; Ying Chen; Linhui Jiang; Cuicui Liu; Haimei Zhu; Dan Qiu; Shui Wang (Environmental Science and Pollution Research, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Architecting versatile NiFe2O4 coating for enhancing structural stability and rate capability of layered Ni-rich cathodes - Yanshuai Yuan; Lei Wang; Qiangchao Sun; Wei Nie; Linhui Chang; Shuangqiang Chen; Hongwei Cheng (Chemical Engineering Journal, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Soil nitrogen substances and denitrifying communities regulate the anaerobic oxidation of methane in wetlands of Yellow River Delta, China - Zihao Wang; Kun Li; Xiaoyan Shen; Feifei Yan; Xinkun Zhao; Yu Xin; Linhui Ji; Qingyue Xiang; Xinyi Xu; Daijia Li; Junhao Ran; Xiaoya Xu; et al. (Science of The Total Environment, 2023)

CACNA1C-AS2 inhibits cell proliferation and suppresses cell migration and invasion via targeting FBXO45 and PI3K/AKT/mTOR pathways in glioma - Tong Cao; Yue Cui; Yingying Wang; Linhui Wu; Ke Yu; Kai Chen; Jun Xia; Yuyun Li; Zhiwei Peter Wang; Jia Ma (Apoptosis, 2022)

Combined addition of chemical and organic amendments enhances plant resistance to aboveground herbivores through increasing microbial abundance and diversity - Linhui Jiang; Michael Bonkowski; Ling Luo; Paul Kardol; Yu Zhang; Xiaoyun Chen; Daming Li; Zhenggao Xiao; Feng Hu; Manqiang Liu (Biology and Fertility of Soils, 2020)

Unexpected rise of ozone in urban and rural areas, and sulfur dioxide in rural areas during the coronavirus city lockdown in Hangzhou, China: implications for air quality - Liqiang Wang; Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Linhui Jiang; Yan Xia; Jiali Li; Weiping Liu; Pengfei Li; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2020)

Phytoplankton growth and microzooplankton grazing in the central and northern South China Sea in the spring intermonsoon season of 2017 - Dawei Chen; Congcong Guo; Linhui Yu; Yuanzhen Lu; Jun Sun (Acta Oceanologica Sinica, 2020)

Danshen formula granule and salvianic acid A alleviate ethanol-induced neurotoxicity - Yujia Li; Hui Chen; Yating Yang; Menglan Niu; Jiaxin Wang; Yuanyuan Wu; Linhui Niu; Hongliang Liu; Dengke Bao (Journal of Natural Medicines, 2020)

Co-expression Network Analysis Revealing the Potential Regulatory Roles of lncRNAs in Alzheimer’s Disease - Jiong Wu; Linhui Chen; Chaobo Zheng; Shanhu Xu; Yuhai Gao; Junjun Wang (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Gibberellin stimulates regrowth after defoliation of sheepgrass (Leymus chinensis) by regulating expression of fructan-related genes - Yueyue Cai; Linhui Shao; Xiuqing Li; Gongshe Liu; Shuangyan Chen (Journal of Plant Research, 2016)

Selection of surfactant in remediation of DDT-contaminated soil by comparison of surfactant effectiveness - Ping Guo; Weiwei Chen; Yueming Li; Tao Chen; Linhui Li; Guanzhu Wang (Environmental Science and Pollution Research, 2014)